DOZ047.34: Oral feeding attainment. (24th June 2019) - Hernandez, K; Davidson, K; Dargie, J; Jennings, R; Manfredi, M
Abstract: Aim: A primary goal of esophageal atresia repair is to establish esophageal continuity to allow for swallowing of secretions, liquid, and food boluses. The transition to oral feeding and acquisition of oral sensorimotor skills following repair of long-gap esophageal atresia (LGEA) can be challenging. The timing of attaining full PO status (F-PO), without need for enteral tube feeding support, can vary greatly. A retrospective study was performed to identify predictors of oral feeding success in children with LGEA. Methods: A retrospective case series was conducted with chart review of patients with a diagnosis of LGEA who underwent Foker process for staged repair from 2012 to 2017. Children with previous failed attempts at esophageal repair or other significant surgeries were excluded. Comparison was made between patients who achieved full PO status (F-PO) within the study follow-up period (minimum of one year postrepair) and those who did not. Results: Twenty-three patients were included: twelve male and eleven female. Eight patients (35%) had an accompanying genetic diagnosis. Thirteen patients (57%) were born prematurely. Six patients (26%) were F-PO at 6 month post-repair; four of which were on an age appropriate diet without restrictions/modifications. Thirteen patients (57%) achieved F-PO by end of the study follow-up period while 43% required supplemental nutrition. Gestational age ≥ 37 weeks ( P   =  0.03), younger age at first PO trial ( P =  0.013), shorter time between Foker 2 and first PO trial ( P =  0.011), consistent PO intake at 6 months post-repair ( P   =  0.02), and fewer total number of airway/esophageal procedures within 1 year post-repair ( P =  0.018) were found to be significantly associated with achieving F-PO. Total number of esophageal dilations within 2 years of esophageal repair and presence of a genetic syndrome were not significantly different between groups. Conclusion: A majority of patients (57%) who undergo repair of LGEA via Foker process will progress to oral feeding; however, the timing of this progression is variable. Predictors of oral feeding success can be used to guide prognosis and identify patients at greatest need of therapeutic services.